2016
DOI: 10.1016/j.jcp.2016.06.034
|View full text |Cite
|
Sign up to set email alerts
|

A convergent Born series for solving the inhomogeneous Helmholtz equation in arbitrarily large media

Abstract: We present a fast method for numerically solving the inhomogeneous Helmholtz equation. Our iterative method is based on the Born series, which we modified to achieve convergence for scattering media of arbitrary size and scattering strength. Compared to pseudospectral time-domain simulations, our modified Born approach is two orders of magnitude faster and nine orders of magnitude more accurate in benchmark tests in 1, 2, and 3-dimensional systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 31 publications
(46 reference statements)
2
70
0
Order By: Relevance
“…condition (18) reduces to α i > max x |∆(x)|. This reproduces the convergence condition found by both Osnabrugge et al 17 and Krüger et al 18 .…”
Section: A Convergent Born Series For Anisotropic Dielectricssupporting
confidence: 87%
See 3 more Smart Citations
“…condition (18) reduces to α i > max x |∆(x)|. This reproduces the convergence condition found by both Osnabrugge et al 17 and Krüger et al 18 .…”
Section: A Convergent Born Series For Anisotropic Dielectricssupporting
confidence: 87%
“…The quantity in the rounded brackets can thus be seen to be a diagonal matrix in the two Fourier space indices. As mentioned above, in a pair of recent papers 17,18 , it was shown that this Born series (5) can be made into a convergent series, the only proviso being that the system exhibits solely dissipation (no gain), and that the permittivity is nowhere singular. To achieve this convergence the authors used two ingenious steps.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…More recently, Wang et al used the Schwartz alternating method and complex variable theory proposed highly accurate analytical solutions for stress and displacement induced by twin tunneling in semi‐infinite ground. Osnabrugge et al proposed an iterative method for numerically solving nonhomogeneous Helmholtz equations, which can achieve convergence of media of arbitrary size and scattering intensity in scattering problems.…”
Section: Introductionmentioning
confidence: 99%